Optimización del proceso de extracción del jugo de la caña de azúcar Saccharum officinarum por medio del Trapiche, para la elaboración de panela artesanal - Alvear Herrera, Wendy Silvana (2024)
Artisanal panela is a product derived from sugar cane and is widely consumed in many regions of the world. In Ecuador it is a very popular product, especially in rural areas; there are around 30,602 hectares for panela production. Optimizing the extraction of cane juice through the mill for the production of artisanal panela implies improving the efficiency and quality of the final product. According to research, it is considered that juice extraction in mills is satisfactory when it ranges between 58% and 63%, however, these percentages are achieved when the equipment is in high wear conditions. The present investigation details the various difficulties, limitations and other aspects that occur in the mills at the time of extraction, since this can negatively influence the juice yield and therefore also the panela production, reaching the conclusion that To optimize this process, we seek to achieve a balance between maximizing the yield of sugarcane juice and minimizing losses, which translates into greater efficiency and production of artisanal panela of high quality and nutritional value. This approach not only benefits producers by increasing profitability, but also guarantees a final product that meets the quality and food safety standards required by consumers.